Is Natural Orifice Specimen Extraction Surgery Really Safe in Radical Surgery for Colorectal Cancer? - Liu, Gang; Shi, Lianghui; Wu, Zehui (Frontiers in Endocrinology, 2022)
Background: The main feature of natural orifice specimen extraction (NOSE) is its avoidance of an auxiliary abdominal incision. Many studies have shown that NOSE surgery has obvious advantages in the treatment of colorectal cancer (CRC), but the safety of NOSE remains controversial. This study aimed to investigate the early safety of transanal NOSE in the treatment of sigmoid colon and upper rectal cancer. Methods: Data from 125 patients diagnosed with sigmoid colon, and upper rectal cancer by gastrointestinal surgery in the First Affiliated Hospital of Wannan Medical College from January 2017 to June 2020 were analyzed. Patients were assigned to two surgical groups: Conventional laparoscopic-assisted radical resection for CRC (CLA, 75cases) and laparoscopic-assisted radical resection for CRC with NOSE (La-NOSE, 50 cases). The following were compared: clinical and pathological characteristics; intraoperative outcomes; bacterial culture, and tumour exfoliation cytology(EC) results of the peritoneal washing liquid; and postoperative complications outcomes. Results: The bacterial culture positive rate was significantly higher in the La-NOSE group (15/50 vs 19/75) than in the CLA group. The exfoliative cytology (EC) rate of the peritoneal wash fluid was 0 in both groups. There was no significant difference in the incidence of postoperative complications between the two groups (La-NOSE group vs CLA group: 3/50 vs 6/75) (p>0.05). Conclusions: Although the incidence of intra-abdominal contamination is high, it does not develop into a severe infectious disease, and does not lead to the implantation of free tumour cells into the abdominal cavity. Therefore, it is safe for the NOSE to treat colorectal cancer.